The Cambridge encyclopedia of stage actors and acting - Williams, Simon 1943- (Cambridge University Press, 2015)
Acting is widely acknowledged to be the central art of the theatre and has a long and vibrant history. With over 1,000 entries, this is the first encyclopedia of stage actors and acting around the world. More than 100 renowned international contributors provide biographical, historical and technical information about actors both familiar and obscure whose work has been crucial in the development of acting methods and traditions from classical theatre to the present day. Entries on key directors, theorists and teachers, and on the elements and genres of acting provide insights into the history of acting as an art and its current practice. Including a chronological list of actors that spans the past 2,000 years and many diverse countries and cultures, this Encyclopedia offers a fascinating and unique overview of acting onstage that will be of interest to anyone who attends or practises theatre. - Simon Williams is a Professor in the Department of Theater and Dance at the University of California, Santa Barbara.
Keywords: Actors -- Encyclopedias; Acting -- Encyclopedias; Theater; Schauspieler; Wörterbuch